Müllerian Agenesis Masquerading as Secondary Amenorrhea - Gloria Tavera; Rina Lazebnik (Hindawi Limited, 2018)
The most common cause of primary amenorrhea is congenital malformation of the Müllerian ducts, including Müllerian agenesis, also known as Mayer-Rokitansky-Küster-Hauser syndrome (MRKH). Most general gynecologists and primary care physicians who see female adolescents will encounter MRKH in their careers. We present the case of an adolescent with MRKH who reported secondary, instead of primary amenorrhea. We discuss the subtleties of diagnosing MRKH, especially when patient history may not always be accurate. Because MRKH had not been included in the differential diagnosis for delayed menses, this patient was initially misdiagnosed. Delayed diagnosis of MRKH may harm patients by delaying assessment of concomitant renal, skeletal, hearing, and cardiac defects, which might otherwise impact the treatment plan.